Caseating regional lymphadenitis complicating BCG vaccination: a report of 6 cases. Issue 12 (December 1982) - Tam, P K; Stroebel, A B; Saing, H; Lau, J T; Ong, G B
Abstract : Six infants had caseating regional lymphadenitis complicating BCG vaccination. There was a delayed onset and a lack of immediate vaccination complications. Three infants had frank abscesses. Additional affected nodes undetected clinically were found at operation in all cases. All lymph nodes contained tubercles, 3 showing acid-fast bacilli, 2 of which grew Mycobacterium bovis. Complete excision followed by antiuberculous chemotherapy produced satisfactory results.